INTERFERENSI LEKSIKAL BAHASA DAERAH KE DALAM BAHASA INDONESIATERHADAP BAHASA REMAJA DI KOTA PALU - NFN Tamrin (Balai Bahasa Sulawesi Tengah, 2015)
One of the phenomena of language contact is interference. Languageinterference can occur at the level of phonology, morphology, sintax, andlexical. This research aims to describe the lexical interference in the locallanguage on the use of Indonesian language by the teenagers in Palu and alsodescribe the lexical factors causing interference local languange intoIndonesian language. The method used is participant’s observation, that is byobservation, recording, and note-taking. The data classified by the types ofinterference and then analyzed by structure. The result shows that the using ofIndonesian language by teenagers in Palu, there is lexical interference, namelylexical interference of local language (mother tongue), lexical interference ofderivative words (Betawi language and Javanese language), and lexicalinterference of foreign language (English). Lexical interference influenced bybilingualism, the low of language loyalty, the prestige of source language andlanguage style, and the influence of mother tongue.